2016
DOI: 10.1590/s1806-92902016001200008
|View full text |Cite
|
Sign up to set email alerts
|

Effects of feed restriction and forage:concentrate ratio on digestibility, methane emission, and energy utilization by goats

Abstract: -This study was carried out to to evaluate how feed restriction and different forage:concentrate ratios affect digestibility, methane emission (using the SF 6 technique), and energy utilization of Anglo-Nubian goats. Fifteen (15) dry and non-pregnant Anglo Nubian goats, averaging 30±2.9 kg body weight, were used. The experiment was divided into two trials, the first of which was designed to study the effects of feed restriction (0% or ad libitum; 15% of feed restriction or equivalent to 85% of ad libitum intak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 26 publications
3
12
0
1
Order By: Relevance
“…This is especially true where concentrates have high starch contents. Though there remain apparent inconsistencies for goats, as witness the comparison between our results and those of Lima et al (2016) and Na et al (2017). As data have accumulated on this topic, opportunities should be taken to exploit the variation in differences among feed qualities that have been used in different experiments to interrogate cognate datasets together so as to tease out dietary variables that have major impact.…”
Section: Resultsmentioning
confidence: 83%
See 2 more Smart Citations
“…This is especially true where concentrates have high starch contents. Though there remain apparent inconsistencies for goats, as witness the comparison between our results and those of Lima et al (2016) and Na et al (2017). As data have accumulated on this topic, opportunities should be taken to exploit the variation in differences among feed qualities that have been used in different experiments to interrogate cognate datasets together so as to tease out dietary variables that have major impact.…”
Section: Resultsmentioning
confidence: 83%
“…However, there were no reductions in methane emissions from goats in response to decreased forage:concentrate ratio in two recent studies, in which a corn and soybean meal-based concentrate was used (Lima et al 2016;Na et al 2017). These conflicting results could be due to differences in forage quality between studies.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Studies conducted in our research group traditionally use estimates of gaseous energy loss as suggested by Blaxter and Clapperton (1965) , resulting in mean value of 8.14 ± 0.433% GE ( Figure 3 ). In this matter, variation in losses due to methane are not well understood because it relies on ruminal microbiota complex interactions, which may vary accordingly feed additives, feed regimen, roughage:concentrate ratio, and measurement methodologies ( Beauchemin et al, 2008 ; Hales et al, 2014 ; Knapp et al, 2014 ; Hill et al, 2016 ; Lima et al, 2016 ; Tapio et al, 2017 ; Hristov et al, 2018 ). Considering that the energy losses in gases comprise mainly methane produced by ruminants, recent studies at UNESP ( Figure 1 ) focused on measuring methane production in goats.…”
Section: Me:de Ratiomentioning
confidence: 99%
“…Os pequenos ruminantes emitem, naturalmente, menos metano por serem seletores de concentrado. A média estimada de emissão de gás metano encontrada no presente estudo foi similar a média obtida por Lima et al (2016) utilizando o método de gás traçador SF6 em cabras. observaram redução na emissão de metano (cerca de 13%) quando utilizaram 41 g/kg MS da dieta de Acacia mearnsii para ovelhas, redução essa semelhante ao presente estudo.…”
Section: Discussionunclassified